Optimal pension plan default policies when employees are biased - Asen Ivanov (Queen Mary University of London, School of Economics and Finance, 2019)
What is the optimal default contribution rate or default asset allocation in pension plans? Could active decision (i.e., not setting a default and forcing employees to make a decision) be optimal? These questions are studied in a model in which each employee is biased regarding her optimal contribution rate or asset allocation. In this model, active decision is never optimal and the optimal default is, depending on parameter values, one of three defaults. The paper also explores how the parameters affect the optimal default and the total loss in the population at the optimal default.
Keywords: D14; D91; J26; J32; 330; optimal defaults; libertarian paternalism; nudging; pension plan design